DESIGNING BASIC SALARY TO IMPROVE EMPLOYEE PERFORMANCE IN AYAMAYAMAN.COM - Hastuti, Primananda Teguh; Putranto, Nur Arief Rahmatsyah (Journal of Business and Management, 2018)
Abstract . Indonesia is one of the developing country in Asia that has many potentials in its food and beverage industry. It gives the biggest contribution for Indonesia non-oil and gas GDP. Restaurants are part of this industry and the number of it being established is increasing each year, especially in Bandung. Ayamayaman.com is one of the restaurants that operating for 24-hours in Bandung. However, the dining in restaurant itself has not been running long and it performance is decreasing. Interview and questionnaire conducted in Ayamayaman.com showed that the decreasing performance caused by employee dissatisfaction toward the compensation system. This research aims to improve employee performance at Ayamayaman.com by designing compensation system based on the competency to determine the basic salary. Current job description was used to be made into job analysis which consists of job description and job specification. Job specification was made by generating competency from compensable factor that describe the requirement for someone to fulfill a job. Point method was used in the next step to calculate the job value from each competency. Salary benchmarking was done next to plan salary that competitive enough in the industry. Validation from the owner is necessary for all of the step conducted in this research. The result of proposed salary was compared with current salary. There are some positions that being paid higher rather than its competency or the opposite. The chosen recommendation was one that fit the budget well and could satisfy the employee so they would perform well.Â Keywords:Â  Basic Salary, Compensation, Competence, Human Resource Management, Point Method